Thermophiles: potential chassis for lignocellulosic biorefinery - Jiang, Yujia; Jiang, Wankui; Xin, Fengxue; Zhang, Wenming; Jiang, Min (Trends in biotechnology (Regular ed.), 2022)
Lignocellulosic thermophiles can speed up lignocellulose hydrolysis and promote efficient degradation, but limited genetic tools and heavy metabolic burden narrow the spectrum of potential products. Constructing synthetic microbial consortia is a potential strategy to address this bottleneck and improves the efficiency of lignocellulosic biorefineries.